Distributed Visual 3-D Localization of A Human Using Pedestrian Detection Algorithm: A Passivity-Based Approach. Issue 22 (2016) - Hatanaka, Takeshi; Funada, Riku; Gezer, Gülsüm; Fujita, Masayuki
Abstract: In this paper, we investigate a distributed visual 3-D localization of a human using a pedestrian detection algorithm for a camera network. We first formulate the problem as a distributed optimization problem. Then, PI consensus estimator-based distributed optimization scheme is extended so that it is applicable to the present problem. We then prove convergence to the optimal solution based on the passivity paradigm. We finally demonstrate the present solution through simulation both in static and dynamic cases.